(untitled) (Journal of Pharmaceutical Negative Results, 2023)
Background: Many couples share the desire to have children, however infertility is regarded as occurring after a year of consistent, unprotected sexual activity. Cultural and familial values have an impact on infertility prevalence, which differs widely. According to estimates, 10% of couples struggle with infertility for a variety of reasons, and the exact cause is frequently unclear. Infertility is typically described by doctors as the inability to get pregnant after a year of regularly having intercourse without the use of contraceptives. Objective: The study sought to ascertain the incidence of these illnesses and associated factors among infertile women because depression and anxiety are among the primary causes of impairment in women. Study design: A cross-sectional study Place and Duration: This study was conducted at Liaquat University of Medical and Health Sciences Jamshoro from December 2021 to December 2022. Methodology: This research includes a total of 150 females. All of the females were infertile and they did a visit to our hospital. A total of 3 types of questionnaires were used; The Beck Depression Inventory, Individual Characteristics, and the Beck Anxiety Inventory. Women with infertility were a part of this research. Moreover, all of the females had to be at least 18 years old or above. Software SPSS version 20 was used to analyze the data using both descriptive and inferential statistics. Results: The average age of the women who were infertile was 39.1 years. The average age of marriage was 20.21 years. The majority of the females were housewives (n=123), representing 82 percent of the total sample. The majority of the women were having an education under a diploma (n=76), representing 50.7% of the participants. A total of 42 percent of the participants had severe depression while 54 percent of the participants had severe anxiety. Conclusion: The results of this study show that infertile women have exceptionally high levels of stress, anxiety, and depression.